2015
DOI: 10.1007/s12011-015-0279-6
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite Interacts with Dibenzo[def,p]chrysene (DBC) at Low Levels to Suppress Bone Marrow Lymphoid Progenitors in Mice

Abstract: Arsenite and Dibenzo[d e f, p]chrysene (DBC), a polycyclic aromatic hyrdrocarbon (PAH), are found in nature as environmental contaminants. Both are known to individually suppress the immune system of humans and mice. In order to determine their potential interactive and combined immunosuppressive effects, we examined murine bone marrow (BM) immune progenitor cells’ responses following combined oral exposures at very low levels of exposure to As+3 and DBC. Oral 5-day exposure to DBC at 1 mg/kg (cumulative dose)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, these studies were conducted at high concentrations that exceeded those expected to result from environmental exposures. Our previous studies demonstrated that DBC is a strong immunosuppressant of murine spleen cells (Lauer et al, 2013), and that As þ3 interacts with DBC at extremely low concentrations to suppress mouse bone marrow pre-B cells (Ezeh et al, 2015). In the present study, the interactions between As þ3 and the metabolites of BaP on genotoxicity in mouse thymus cells were analyzed within the nanomolar range of exposure, which are more representative of environmental exposures.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, these studies were conducted at high concentrations that exceeded those expected to result from environmental exposures. Our previous studies demonstrated that DBC is a strong immunosuppressant of murine spleen cells (Lauer et al, 2013), and that As þ3 interacts with DBC at extremely low concentrations to suppress mouse bone marrow pre-B cells (Ezeh et al, 2015). In the present study, the interactions between As þ3 and the metabolites of BaP on genotoxicity in mouse thymus cells were analyzed within the nanomolar range of exposure, which are more representative of environmental exposures.…”
Section: Discussionmentioning
confidence: 89%
“…PAHs to increase the suppression of progenitor pre-B cell formation in murine bone marrow at very low concentrations both in vitro and in vivo (Ezeh et al, 2014(Ezeh et al, , 2015. Synergistic immunosuppression of T-dependent antibody responses by different PAHs and As þ3 spleen cells were also observed (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined in vitro As exposure and immune function in animal models [21, 22, 27, 28, 4043] and PBMC exposed in vitro [4447]. In a review of the literature we did not find any studies that examined the association of UAs/Cr with CSM expressed by PBMC in adults.…”
Section: Discussionmentioning
confidence: 89%
“…Since large PAHs, such as benzo[a]pyrene (BaP) are complete carcinogens and known to induce DNA damage, we postulated that they might act synergistically with As in humans. Indeed, in in vivo animal models at some doses, there is a synergy between As and PAHs [27], and this synergy is easily observed in the thymus following in vitro exposures [28]. However, following chronic exposure to As in men, we found no evidence of synergy with PAHs for TCP or cytokine production in PBMC [19].…”
Section: Introductionmentioning
confidence: 86%
“…Because the immune system plays an important role in protecting against cancers and infection, the purpose of the present study was to assess the effects of chronic arsenic exposures on functional measures of the human immune system, including TCP and cytokine production, measured in HPBMC from males living in Bangladesh. We also examined the role of PAH exposure, as it is also associated with immune modulation and our previous work in mouse models demonstrated that there may be important interactions between PAHs and arsenic [16, 17]. We examined the influence of PAH exposure, as indicated by in vivo PAH-DNA adducts, on ex vivo immune function and the potential interactions between PAH-DNA adducts and urinary arsenic in statistical models.…”
Section: Introductionmentioning
confidence: 99%